2012
DOI: 10.1002/app.36685
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliated/intercalated silicate/hot styrene butadiene rubber nanocomposites: Structure–properties relationship

Abstract: Rubber nanocomposites based on hot styrene-butadiene rubber (SBR) and organophilic layered silicate were prepared via mechanical mixing followed by compression molding. Varying amount of organically modified nanosilicate, 2.5, 5, 10, and 15 parts per hundred of rubber (phr), was added to the SBR matrix to examine the influence of nanosilicate on morphology and structure-property relationships. The morphology of nanocomposites was studied by X-ray diffraction and transmission electron microscopy which reveal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…They suggest that the better thermal stability of nanocomposites can be attributed to the nanoscale montmorillonite layers preventing out‐diffusion of the volatile decomposition products. . Kuila et al reported that the increase in the thermal stability of gra‐phene/polyethylene composite system was due to the high aspect ratio of the monodispersed graphene layers, which acted as a barrier and inhibited the emission of small gaseous molecules.…”
Section: Resultsmentioning
confidence: 99%
“…They suggest that the better thermal stability of nanocomposites can be attributed to the nanoscale montmorillonite layers preventing out‐diffusion of the volatile decomposition products. . Kuila et al reported that the increase in the thermal stability of gra‐phene/polyethylene composite system was due to the high aspect ratio of the monodispersed graphene layers, which acted as a barrier and inhibited the emission of small gaseous molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays rubber–clay nanocomposites have been developed by various methods, including in situ polymerization intercalation , solution intercalation , melt intercalation , and cocoagulating rubber latex and clay aqueous suspension (namely latex compound method ). From an industrial point of view, melt intercalation is the most direct, cost effective, and environmentally friendly (no organic solvents involved) method to produce phillosilicate–rubber nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…4 Demand for synthetic rubber in 2020 according to rubber types, and their respective applications. [49][50][51][52][53][54][55][56][57] disposal management are among the problems faced globally. [66][67][68] The high demand and usage volume for rubber products created a serious problem, as the rate of biodegradation of synthetic rubbers is extremely low, and they persist in landlls or nature for almost indenitely aer being discarded, causing environmental pollution and increase in landll sizes.…”
Section: Recent Progress In Enhancing Biodegradation Of Synthetic Rub...mentioning
confidence: 99%